Seeking the Sources of Heart of Darkness: the African Narratives of late-Victorian Explorers and Journalists - Andrew Griffiths (Continents manuscrits)
This paper begins by briefly outlining the argument that Heart of Darkness should be read as something like a palimpsest – a palimpsest is, of course, a medieval document scribed onto parchment that has previously been inscribed with other texts and still bears their traces. It argues that Heart of Darkness dramatizes various acts of writing or representation that are later effaced and overwritten or rewritten. In doing this, the novella continually gestures beyond itself to source material that too has been effaced and rewritten. The paper then takes an archaeological approach, exploring just what that source material might be and how its traces are legible in Heart of Darkness. Henry Morton Stanley’s exploration narratives are identified as significant sources, which Conrad seeks to efface and overwrite. The paper further argues that debates running in British journalism through the 1890s, which Conrad discussed in correspondence with R.B. Cunninghame Graham, shaped the tone and atmosphere of the text. Finally, the paper outlines the possible relationship of Heart of Darkness to the wider field of writing on African travel and exploration.